The roles of university in responding to psychosocial issues in the community: the case of two Islamic universities - Abdul Rahman, Shukran (2019)
Universities, including faith-based universities, are institutions which are entrusted to equip individuals with necessary competencies, so as to empower the society with intellectual capabilities. This paper discusses the roles of two Islamic universities in responding to psychosocial issues in the community, hence, in turn, being contributive to sustainable development goals. The author has sourced information from the documents which describe the ethos of two Islamic universities, as well as literature and relevant documents which report the universities’ community engagement practices. The paper presents the three functions of universities, namely the University Intellectual, Educational, and Social Functions. The functions can be collectively accomplished through the involvements of professional community, learned community, learning community, and community at large. The paper shed lights on the extent of community engagement activities vis a vis the SDGs